Upaya Pengembangan Sektor Pariwisata Melalui Peran Kreativitas Pemuda - Arif Akbar; R. Hamdani Harahap; Rujiman Rujiman (Universitas Medan Area, 2021)
The purpose of this study was to see the creativity of youth in developing the Lake Toba tourist area in Muara Regency. The method used in this study is a descriptive method with a qualitative approach. This study looks at how the tourist attraction of Muara Regency in terms of attractiveness, amenities, accessibility, and support. There are three roles and creativity carried out by youth as the motor of the development of the Lake Toba Region in Muara Regency. First, youth creativity as a driving force, in which youth implementation forms the Muara Inspirasi Community as a forum for implementing creative activities that functions to optimize all existing youth resources. Second, youth creativity as a motivator where in practice the youth continue to encourage and hope that the people living in Muara Regency to build an independent economy by making local businesses such as making lodging, restaurants and making ulos. In addition, the youth of Muara Insipirasi also motivate school-age children to increase their knowledge through reading houses. The third role and creativity is youth as innovators where Muara Inspirasi youth provide an overview of innovation to ulos weavers to become promotional media and historical stories of Lake Toba in Muara Regency. Muara Insipirasi youth also motivate school-age children to increase their knowledge through reading houses. The third role and creativity is youth as innovators where Muara Inspirasi youth provide an overview of innovation to ulos weavers to become promotional media and historical stories of Lake Toba in Muara Regency. Muara Insipirasi youth also motivates school-age children to increase their knowledge through reading houses. The third role is youth as innovators where Muara Inspirasi youth provide an overview of innovation to ulos weavers to become promotional media and historical stories of Lake Toba in Muara Regency.